Systematic Review and Network Meta-Analysis on Treating Hormone Receptor-Positive Metastatic Breast Cancer After CDK4/6 Inhibitors - Neha Pathak; Abhenil Mittal; Sudhir Kumar; Chitrakshi Nagpal; Eitan Amir; Partha Haldar; Bharath B. Gangadharaiah; Akash Kumar; Ashutosh Mishra; Atul Batra (Current Oncology)
Introduction: The optimal treatment of estrogen receptor-positive (ER +) metastatic breast cancer (MBC) after progression on cyclin-dependent 4/6 kinase inhibitors (CDK4/6i) is unknown. Methods: We conducted a systematic review and network meta-analysis (NMA) of phase-II/-III randomized trials of ER + MBC post CDK4/6i + ET progression. We calculated the hazard ratio (HR) for progression-free survival (PFS) and overall survival (OS) using generic inverse variance and odds ratios (ORs) using the Mantel–Haenszel method for adverse events (AEs) with Review-Manager version-5.4. NMA was executed using WINBUGS (Microsoft Excel). Three molecular subgroups were analyzed: HER2-low, PI3K/AKT/mTOR, and the ESR1 mutation subgroup for selective estrogen receptor degrader (SERD). Results: A total of 14 studies were included. In the HER2-low group, Sacituzumab govitecan and trastuzumab deruxtecan had a similar efficacy (HR, 95% CI): PFS (0.98; 0.63–1.43) and OS (1.08; 0.76–1.55). In PI3K/AKT/mTOR-altered cases, capivasertib was superior to alpelisib PFS (0.77; 0.53–1.12), and OS (0.80; 0.48–1.35). SERDs had worse PFS and OS versus ongoing CDK 4/6i (ribociclib). Conclusion: No therapy emerged as the unequivocal choice in the post-CDK 4/6i domain in unselected subgroups. In the HER2-low population, a similar efficacy and different toxicity spectrum was seen. In AKT-altered tumors, capivasertib was less toxic than alpelisib. PROSPERO ID: CRD4202236412.